Meminimalkan Biaya Transportasi Penentuan Rute Terpendek Pengiriman Barang Menggunakan Metode Generate And Test - Mahrizon, Dedi (LPPM UNIKA Santo Thomas Medan, 2023)
Transportation plays an important role in the delivery of goods both in the far and near reaches. To minimize the distance traveled, appropriate planning and calculations are needed to save time and costs in delivering goods to the destination. The process of determining the shortest route is included in the science of artificial intelligence in solving search problems. The science of intelligence which is well-known in determining the shortest route, namely Generate and Test, Traveling Salesman Problem (TSP) or understood as the search for the shortest path is often implemented in the real world because this method is able to solve problems and produce algorithms that can be applied in everyday life. The main objective of this research is to implement the search concept Generate and Test in helping users in shipping goods to save time, lower costs. The Generate and Test Algorithm is a combination of Depth First Search and Backtracking. The results of this study obtained the longest value of 113 with the combination f (A-D+F+I+J+M+Q+S+T)_= 20+18+9+20+7+10+13+16=113 and shortest path value 61 which starts with path f (A-C+I+P+T )=11+20+17+13=61 by obtaining information on the smallest shortest path, namely 61, can be used as the final state to be passed in shipping goods, so This path can be used as a reference to obtain the final solution.